Identifikasi dan Patogenisitas Agen Bakteri Penyebab Penyakit Busuk Batang pada Buah Naga (Hylocereus sp.) - Riziq Ilham Nur Fahmi; Uci Cahlia; Risky Hadi Wibowo; Sipriyadi Sipriyadi (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
The increasing intensification of dragon fruit (Hylocereus sp.) cultivation is followed by an increase in disease attacks that have the potential to reduce plant productivity. This study aims to isolate, identify, and test the pathogenicity of bacteria that cause dragon fruit stem rot in Pematang Donok Village, Kepahiang, Bengkulu. Bacterial isolation was carried out from disease-infected stem tissue, followed by isolation purification. Bacterial identification was carried out based on colony morphology and Gram staining, while pathogenicity and hemolysis tests were carried out on potatoes and blood agar media, respectively. The data were analyzed descriptively qualitatively through observation of colony morphological characteristics and Gram staining, as well as pathogenicity tests on potatoes and hemolysis tests on blood agar. The isolation results obtained two bacterial isolates, namely isolates BBNK1 and BBNK2 with different colony morphology characteristics. Both isolates are Gram-positive bacteria with bacillus and coccus cell shapes. Pathogenicity tests on potatoes showed that both isolates were able to cause soft rot symptoms such as tissue softening, discoloration, and mucus formation compared to the control. Hemolysis tests showed that only isolate BBNK1 showed hemolytic activity with the formation of a clear zone around the isolate. The findings of this study offer foundational data to support future research on molecular identification and the development of more environmentally friendly and sustainable disease management strategies.